Transforming animal waste into a friendly and economically sustainable adsorbent for removing organic pollutants from aqueous wastewater - Boujemaa Soubai; Az-iddin Chham; Belaid Selhami; Mohamed Akouibaa; Smail Ait Said Ali; Abdellah Anouar El foulani; Mohamed Tahiri (Case Studies in Chemical and Environmental Engineering)
The removal of crystal violet (CV) and methylene blue (MB) from an aqueous solution was successfully accomplished using biochar derived from Moroccan sheep manure (SM). Process optimization revealed adsorption efficiencies of 96.77 % and 98.95 %, with maximum adsorption capacities of 244.08 mg/g and 295.14 mg.g−1 for MB and CV dyes, respectively. This was achieved at pH 11, with an adsorbent dose of 0.5 g.L−1 at 40 μm, over a 120 minutes at 25 °C. The results indicate that the Freundlich isotherm model is the best fit for both dyes. The pseudo-second-order model accurately describes the kinetics of the processes studied for both dyes. The thermodynamic characteristics clearly demonstrated the endothermic and spontaneous nature of the dye elimination. The ΔH° values of 34.3293 and 31.3338 KJ.mol−1for the MB and CV dyes respectively, suggest that physisorption and chemisorption may be involved in the adsorption process. The re-adsorption study revealed that biochar can be reused for up to 5 cycles with both dyes. Adsorption of dyes onto biomass is facilitated by electrostatic, π-π, n-π and hydrogen bonding interactions. Additionally, SMB300 has been identified as an effective, cost-efficient, and environmentally friendly material for removing cationic dyes.